B-lines by lung ultrasound is associated with pulmonary symptoms and cardiac function in acute malaria: a prospective cohort study. (14th October 2021) - Wegener, A; Holm, A; Gomes, L; Lima, K; Matos, L; Vieira, I; Kaagaard, M; Souza, R; Marinho, C; Sorensen, T; Silvestre, O; Brainin, P
Abstract: Background: Malaria patients are at risk of cardiopulmonary complications, but diagnosis and management are difficult in resource limited environments. B-lines by lung ultrasonography (LUS) can identify pulmonary alterations, however, little is known about the usefulness in malaria. Purpose: We aimed to investigate the occurrence of B-lines in acute malaria patients at baseline and at follow-up, and whether they are associated with shortness of breath and impaired left ventricular ejection fraction (LVEF). Methods: Adult patients with non-severe acute malaria were prospectively enrolled from June to December 2020 in community healthcare clinics in a remote area. Patients were age- and sex-matched to controls without a prior history of malaria. We examined patients prior to anti-malaria treatment and at follow-up. Malaria treatment was administered according to national guidelines. Patients were excluded if they were pregnant, had concomitant infections or recent chest trauma. Patients underwent LUS (8-zones), echocardiography and peripheral blood smear. Measurements were blinded to clinical variables and outcomes. Results: We included a total of 99 patients (median age 40±15 years, 55% men). Patients suffered from Plasmodium vivax (n=75), P. falciparum (n=22), and a mix of the two (n=2) and median parasite density was 1, 595 parasites/mL (interquartile range [IQR] 528–6, 585/mL). Follow-up was completed in 71 patients and the median follow-up time was 31 days (IQR 27–40 days). Patients with acute malaria had significantly more B-lines at baseline than matched controls (P-value<0.001) and fewer B-lines at follow-up (P-value<0.001) (Figure 1). In acute malaria patients, number of B-lines at baseline correlated significantly with shortness of breath (OR 1.20, [1.04 to 1.39], P-value=0.01) and with LVEF (adjusted for age and sex: +8% [+1% to +15%], P-value=0.016 per 1% decrease in LVEF). There was no correlation between number of B-lines and parasite density (+2% [−5% to +11%], P-value=0.53 per 1000 increase in parasite density). Conclusion: B-lines detected by LUS are more frequent in patients with acute malaria than in age- and sex-matched controls and decrease in response to treatment. B-lines also correlate with shortness of breath and lower LVEF at baseline. Because LUS is a quick and accessible examination, it may potentially facilitate risk stratification and therapeutic decisions regarding cardiopulmonary complications in patients with acute malaria. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Danish Heart Association